From Pamphlet to Utopian Caliphate: Utilization of Mass Media and Promotion of the Caliphate Ideology among Muslim Youth in Solo - Muhammad Rosyid; Ramita Paraswati (Jurnal Dialog, 2023)
The ideology of the caliphate is being intensely discussed in the Indonesian Muslim community, following the appearance of the Khilafatul Muslimin (KM) convoy that invites to welcome the emergence of the caliphate. This study focuses on examining the response of Muslim youth in Solo to the ideas of the caliphate, which are widely mushrooming in the mass media, especially in the Kaffah bulletin, one of the bulletins that disseminate the caliphate ideology on various platforms. This research uses the descriptive qualitative method, which provides descriptive data from the analysis results on the Kaffah in as many as 256 editions. The data collection technique used in this research is critical content analysis, interview, focus group discussion, and documentation. This paper argues that Kaffah has successfully promoted and mobilized young people to be attracted to the idea of the caliphate because they could neatly package religious doctrines with the hot issues being discussed. However, in brainwashing the public through the pamphlet, Kaffah is frequently questionable, quoting dhaif hadiths, distorting opinions, and utilizing fake news to support statements propagated by their affiliates.